30+4y-11=14y-13-2y

Simple and best practice solution for 30+4y-11=14y-13-2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 30+4y-11=14y-13-2y equation:


Simplifying
30 + 4y + -11 = 14y + -13 + -2y

Reorder the terms:
30 + -11 + 4y = 14y + -13 + -2y

Combine like terms: 30 + -11 = 19
19 + 4y = 14y + -13 + -2y

Reorder the terms:
19 + 4y = -13 + 14y + -2y

Combine like terms: 14y + -2y = 12y
19 + 4y = -13 + 12y

Solving
19 + 4y = -13 + 12y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-12y' to each side of the equation.
19 + 4y + -12y = -13 + 12y + -12y

Combine like terms: 4y + -12y = -8y
19 + -8y = -13 + 12y + -12y

Combine like terms: 12y + -12y = 0
19 + -8y = -13 + 0
19 + -8y = -13

Add '-19' to each side of the equation.
19 + -19 + -8y = -13 + -19

Combine like terms: 19 + -19 = 0
0 + -8y = -13 + -19
-8y = -13 + -19

Combine like terms: -13 + -19 = -32
-8y = -32

Divide each side by '-8'.
y = 4

Simplifying
y = 4

See similar equations:

| 2x+35=7x+10 | | f(46)=4x-2 | | -13.00+2x=11.00 | | (7x^3+4x^2-9x+10)(8x^3-5x^2+11x-6)=0 | | 10+16x-16=12x-6 | | -3(-2)+7= | | 5(x+3)/3=4x-2 | | -89=-3(4+3p)-5 | | -5(-2)+9= | | (243)^(3/5) | | 15x-9=7+6-2x | | 243^3/5 | | -5(-1)+9(-1)= | | 50+15x=25x | | -3+2n=n+3 | | 49=-6x+2x+1 | | 5c-4c=c+20 | | -3.5-(-6.6)= | | -5(-2)+9(-2)= | | 7h/h | | 7x^2+9x-3x^4+6=0 | | 9h^2/h | | xc^2-8=a^2+5x | | 25x=15x | | 1-6z=-71 | | 15=9+t | | 8x^3y^2+7xy-4x^4y^3=0 | | 73-18+8w=67 | | x/(1-x)=28/38 | | 2(2x-1)+2(x+2)=(x+7)+(2x+5)+(2x+7) | | x/(1-x)=28/18 | | x/(1-x)=38/28 |

Equations solver categories